PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PANJANG GARIS SINGGUNG PERSEKUTUAN DUA LINGKARAN DI KELAS VIII SMP NEGERI 19 PALU - Paloloang, Muhammad Fachri Baharuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain a description about application of Problem Based Learning (PBL) that can improve students learning outcomes on length of tangent line to two circles in class VIII SMPN 19 Palu. The type of this research is classroom action research. The design of this research referred to Kemmis and Mc. Teggart’s design. This research was conducted in two cycles. The results of this research indicating that through the application of PBL that can improve student learning outcomes, by following the steps, as follow (1) orientation the students at the problem of using video or animation, (2) organize the students to learn, (3) assist in the investigation of individual and group, (4) develop and present work result and, (5) analyze and evaluate problem-solving process.